(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article reveals the theoretical foundations and practical approaches to developing self-regulation skills in students during the educational process. It also analyzes effective methods for fostering qualities such as independent thinking, responsibility, self-control, and goal-oriented activity in the course of learning. The article highlights key factors in forming self-regulation abilities in learners based on modern pedagogical technologies, a learner-centered approach, and reflection methods.